If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -41 = -5(x + 4) Reorder the terms: -41 + -2x = -5(x + 4) Reorder the terms: -41 + -2x = -5(4 + x) -41 + -2x = (4 * -5 + x * -5) -41 + -2x = (-20 + -5x) Solving -41 + -2x = -20 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -41 + -2x + 5x = -20 + -5x + 5x Combine like terms: -2x + 5x = 3x -41 + 3x = -20 + -5x + 5x Combine like terms: -5x + 5x = 0 -41 + 3x = -20 + 0 -41 + 3x = -20 Add '41' to each side of the equation. -41 + 41 + 3x = -20 + 41 Combine like terms: -41 + 41 = 0 0 + 3x = -20 + 41 3x = -20 + 41 Combine like terms: -20 + 41 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| (6x-32)+(2x-20)=180 | | 10x-19=4x+1 | | 5.8+(-2.5)=x | | 12-[4-2(y+1)]=2y+6 | | 6-3.98=x | | (y-12)+(3y-8)=180 | | 28a^2-192a-28=0 | | 7w-5=3w+11 | | 9x+29=93-5x | | 10-(-10)-7-5=x | | 8.5x-3.5x=-94 | | (-11)-8+1-(-6)=x | | 4x+2=x-11 | | (-3)+5+(-5)+12=x | | x/2+3=1/2 | | 6+(-7)+(-5)-(-2)=x | | 6y=45-3y | | 7+(-1)+12-7=x | | (-11)-(-14)+7=x | | 9+6(2)7n= | | 0.5x-1.4=1.1 | | (-7)-(-2)-9=x | | -6-1=-32y+32 | | 16-(-13)-(-5)=x | | 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 |